Effect of PVDF binder on the performance of Zn-Ni carbonate hydroxide hydrate battery electrode in supercapattery - Pershaanaa M.; Farhana N.K.; Kamarulazam F.; Loh K.H.; Prasankumar T.; Bashir S.; Ramesh K.; Ramesh S. (Elsevier Ltd, 2025)
In the midst of enhancing the energy density of energy storage devices, a novel approach has emerged involving the hybridisation of supercapacitors and batteries to fabricate energy storage systems with superior energy density, power density, and longevity. A critical aspect in boosting the energy density of these devices lies in the performance enhancement of the active materials utilised. Therefore, this work developed a densely packed zinc-nickel carbonate hydroxide composite resembling marigold flowers (Zn/NCHH) to facilitate rapid redox reactions. Together, this work highlights the impact of the direct deposition technique over conventional binder-based technique in terms of electrochemical performance. It was revealed that the direct growth of Zn/NCHH led to a four-fold increase in specific capacity (1215.30 C g?1 at 3 A g?1) compared to binder-based electrodes. This enhancement was attributed to the uniform and robust network formed between the active materials and the substrate through direct deposition, resulting in improved mechanical adhesion, electrolyte ion percolation, increased exposed active sites, reduced charge transfer resistance, and exceptional reproducibility. Conversely, the introduction of binders hindered the network formation, leading to elevated resistance, material degradation over charge/discharge cycles, severe agglomeration limiting active site exposure, resulting in compromised electrochemical performance. The assembled supercapattery utilising Zn/NCHH/NF//AC/NF demonstrated remarkable maximum energy density and power density of 31.00 Wh kg?1 and 6243.67 W kg?1, respectively, with excellent cyclic stability (96 %) over 9000 charge-discharge cycles. Additionally, it exhibited an enhanced coulombic efficiency of 112 % over the 9000 cycles. ? 2024 Elsevier B.V.